Validasi Metode Analisis Matriks Patch Domperidon Maleat dengan Perbedaan Polimer Menggunakan Spektorfotometri UV-Vis - Shesanthi Citrariana; Oktavia Indrati; Puspa Dwi Pratiwi; Ita Nurma Sari; Ari Wibowo (Universitas Muhammadiyah Surakarta, 2021)
Uv-Vis spectrophotometry is an analytical method that can be used to determine the levels of domperidon maleate contained in transdermal patches with different polymers. The analysis method needs to be validated to prove that it can provide measurement results that match its designation. The purpose of this study is to prove that uv-vis spectrophotometry methods can provide the specificity, linearity, thoroughness, and precision that meet the requirements. In this study, linearity was known by calculating the r value on the curve of the relationship between levels and absorbance. Precision is obtained based on rsd value. Accuracy is calculated based on the return value. Selectiveity is known by means of identity confirmation that calculates the absorbance ratio at different wavelengths. The results showed that the method meets the requirements with a value of r=0.999; RSD precision results at a level of 10 ppm obtained RSD 0.236%. The accuracy values of 80%, 100%, and 120% in the matrix of transdermal domperidon maleate patches with PVA and PVP polymers respectively recovery was 99.50%, 101.15%, and 99.13%.. In the matrix of transdermal patches domperidon maleate with polymers HPMC and Na-CMC respectively recovery was 100.91%, 100.31%, and 100.67%. In the matrix of transdermal domperidon patches with HPMC and EC polymers respectively recovery was 98.00%, 98.00%, and 99.00%. The identity confirmation results on the transdermal domperidon patch matrix with PVA and PVP polymers, HPMC and Na-CMC, as well as HPMC and EC respectively have ratio value close to the standard solution with an average value of 0.800; 0,806; and 0.808. It can be concluded that the method of analyzing the levels of domperidone maleate in matrix of transdermal patches has qualified for good validity.